La rencontre pacifique de deux mondes chrétiens Les monastères de la Péribleptos et de la Pantanassa à Mistra - Louvi-Kizi, Aspasia (Suppléments du BCH, 2022)
In publishing this book, an early version of which was first published under the auspices of the Academy of Athens, the French School at Athens highlights the research work of Aspasia Louvi-Kizi, an eminent specialist in the Frank and Byzantine Peloponnese, whose work reveals all of the complexity of the architectural forms, influences and models at work in the monuments of the medieval Byzantine city of Mystras. Out of all of the architecture created by the despotic couple formed by Manuel Cantacuzène (1349-1380) and his wife Isabelle de Lusignan, who were instrumental in turning Mystras into a centre of power, Aspasia Louvi-Kizi focuses on two of the city's most iconic monuments, the monasteries of Peribleptos and Pantanassa, proposing a new history of their construction. Their architecture incorporates elements of Frank art, meaning western or gothic art, which were foreign to the local Byzantine tradition. The gothic aspect of Mystras' architecture, as distinct from the Franco-Byzantine influences in the neighbouring crusader principality of Achaea, has more to do with Western art in Cyprus, and its introduction by Isabelle to the Peloponnese was to prove decisive. The Western elements that decorate the facades of clocks and towers, combined with the Byzantine features to constitute a concrete expression of the despotic couple's pro-Western politics, in line with the imperial politics of Constantinople at the time. In the fragmented and multipolar world of the Eastern Mediterranean on the eve of the Ottoman conquest, this book highlights the role Mystras played as a centre of power in the region and, in doing so, contributes to a fresh take on the city as a whole. By continuing the international conversation about a renowned site, the French School at Athens shows its commitment to a multi-layered approach that reveals the complexity of the interactions at work in the history of the Greek world in transition.